Development of Environment-Based Augmented Reality Learning Media to Improve Students’ Scientific Creativity Abilities - Tiana, Ainun; Wicaksono, Iwan; Hanafi, Hafizul Fahri; Sutarto, Sutarto; Indrawati, Indrawati (International Journal of Research and Community Empowerment, 2026)
Scientific creativity is an important competency in 21st-century science education. However, many students still show limited ability to generate original and flexible scientific ideas. This study aims to develop an environment-based augmented reality (AR) learning media and to test its validity, practicality, and effectiveness in enhancing students' scientific creativity. A research and development design using the ADDIE model was used. Participants were junior high school students who used the developed Augmented Reality media during science learning. Data were collected through expert validation sheets, observation sheets, scientific creativity tests, and student response questionnaires. The results showed that the media achieved a high level of validity (90%), was very practical to implement (94%), and demonstrated moderate effectiveness in enhancing scientific creativity (N-gain = 0.68). This research contributes to the field by providing a specialized pedagogical framework that bridges abstract environmental concepts with interactive digital visualization, offering a scalable solution to stimulate divergent thinking in science classrooms. Furthermore, this study supports the achievement of Sustainable Development Goals Goal 3 Good Health and Well-being and Goal 4 Quality Education by enhancing students’ higher-order thinking skills through innovative technology-based learning. These findings indicate that environment-based Augmented Reality is effective in improving students’ scientific creativity and supporting sustainable development.